Perspektif Kemanfaatan Hukum terhadap Kejahatan Kohabitasi Pasal 412 Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana - Lase, Agilber Gamaliel; Zulyadi, Rizkan; Mubarak, Ridho (JUNCTO: Jurnal Ilmiah Hukum, 2025)
The phenomenon of cohabitation or "kumpul kebo" has attracted public concern in Indonesia, a society that upholds moral values. Article 412 of Law Number 1 of 2023 concerning the Criminal Code (KUHP) criminalizes cohabitation, reflecting a shift from social norms to legal regulation. This study employs a normative juridical approach with document analysis to examine the legal substance of cohabitation and its usefulness in the Indonesian social context. The data sources include statutory regulations, court decisions, and relevant legal literature. The findings indicate that the criminalization of cohabitation provides a clear legal basis, safeguards public morality, and harmonizes legal enforcement nationwide. However, the absence of an explicit definition of "living together as husband and wife" creates interpretive ambiguity, which may pose challenges in legal implementation. Therefore, while this legal provision contributes to the enforcement of social and legal norms, its application must be carefully balanced with considerations of justice and human rights.